2016
DOI: 10.1002/jnr.23843
|View full text |Cite
|
Sign up to set email alerts
|

All‐trans retinoic acid improved impaired proliferation of neural stem cells and suppressed microglial activation in the hippocampus in an Alzheimer's mouse model

Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disorder characterized by cognitive impairment with neuronal loss. The number of patients suffering from AD has increased, but none of the present therapies stops the progressive symptoms in patients with AD. It has been reported that the activation of microglial cells induces harmful chronic inflammation, leading to neuronal death. Furthermore, the impairment of adult neurogenesis in the hippocampus has been observed earlier than amyloid plaque for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…A large number of studies have shown that inhibition of microglial cells activation improves the neurogenesis and cognitive performance [ 23 , 24 ]. In particular, inhibition of microglia activation by minocycline (a broad spectrum antibiotic, anti-inflammatory drug) has a profound neuroprotective effect associated with the improvement of spatial memory and neurogenesis during neuroinflammatory conditions [ 3 , 14 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that inhibition of microglial cells activation improves the neurogenesis and cognitive performance [ 23 , 24 ]. In particular, inhibition of microglia activation by minocycline (a broad spectrum antibiotic, anti-inflammatory drug) has a profound neuroprotective effect associated with the improvement of spatial memory and neurogenesis during neuroinflammatory conditions [ 3 , 14 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the memory deficits induced by a full dose of Aβ 1-42 in the MVAD rats were apparent at 30 days but not 80 days post-injection. Previous studies have demonstrated that intracerebral fibrillar Aβ 1-42 induces proliferation and activation of microglia [37, 38] and RA suppresses microglial activation in an AD mouse model [39], so it is likely that MVAD accelerates the activation of microglia following Aβ 1-42 injection. A full dose of Aβ 1-42 might as well facilitate the damage of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined whether loss of RALDH2 expression affected microglial development. Microglial activation, including increased proliferation, can be mitigated by RA signaling (Dheen et al, 2005;Takamura et al, 2017), and changes in microglial function could impact OL development. By performing immunofluorescence staining for ionized calcium-binding adaptor molecule 1 (IBA1) at P7, 14, and P21, we found no significant differences between genotypes in terms of IBA1 ϩ cell number ( Fig.…”
Section: Loss Of Raldh2 Reduces Nsc Survival and Gli1 Expression In Tmentioning
confidence: 99%